Stable CDK12 Knock-Out Ovarian Cancer Cells Do Not Show Increased Sensitivity to Cisplatin and PARP Inhibitor Treatment - Chilà, Rosaria; Chiappa, Michela; Guffanti, Federica; Panini, Nicolò; Conconi, Donatella; Rinaldi, Andrea; Cascione, Luciano; Bertoni, Francesco; Fratelli, Maddalena; Damia, Giovanna (Frontiers in Oncology, 2022)
Cyclin-dependent kinase 12 (CDK12) is a serine/threonine kinase involved in the regulation of RNA polymerase II and in the transcription of a subset of genes involved in the DNA damage response. CDK12 is one of the most mutated genes in ovarian carcinoma. These mutations result in loss of function and can predict the responses to PARP1/2 inhibitor and platinum. To investigate the role of CDK12 in ovarian cancer, CRISPR/Cas9 technology was used to generate a stable CDK12 knockout (KO) clone in A2780 ovarian carcinoma cells. This is the first report on a CDK12 null cell line. The clone had slower cell growth and was less clonogenic than parental cells. These data were confirmed in vivo, where CDK12 KO transplanted cells had a much longer time lag and slightly slower growth rate than CDK12-expressing cells. The slower growth was associated with a higher basal level of apoptosis, but there were no differences in the basal level of autophagy and senescence. While cell cycle distribution was similar in parental and knockout cells, there was a doubling in DNA content, with an almost double modal number of chromosomes in the CDK12 KO clone which, however did not display any increase in H2AX, a marker of DNA damage. We found partial downregulation of the expression of DNA repair genes at the mRNA level and, among the downregulated genes, an enrichment in the G2/M checkpoint genes. Although the biological features of CDK12 KO cells are compatible with the function of CDK12, contrary to some reports, we could not find any difference in the sensitivity to cisplatin and olaparib between wild-type and CDK12 KO cells.